Lesotho : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1994)
This paper reviews economic developments in Lesotho during 1990-94. During the six years (1988/89-1993/94) under the IMF-supported programs, real GDP growth has averaged 6.5 percent, and investment has risen rapidly, owing to activities related to the Lesotho Highlands Water Project and substantial foreign private direct investment. Real gross national product growth averaged only 3.3 percent, owing to a decline in remittances, as a major retrenchment of mine workers in South Africa occurred during this period. The government's budgetary position improved substantially during the six-year period.